2012
DOI: 10.1371/journal.pone.0029597
|View full text |Cite
|
Sign up to set email alerts
|

Capture of Neuroepithelial-Like Stem Cells from Pluripotent Stem Cells Provides a Versatile System for In Vitro Production of Human Neurons

Abstract: Human embryonic stem cells (hESC) and induced pluripotent stem cells (iPSC) provide new prospects for studying human neurodevelopment and modeling neurological disease. In particular, iPSC-derived neural cells permit a direct comparison of disease-relevant molecular pathways in neurons and glia derived from patients and healthy individuals. A prerequisite for such comparative studies are robust protocols that efficiently yield standardized populations of neural cell types. Here we show that long-term self-rene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
389
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 263 publications
(407 citation statements)
references
References 29 publications
(45 reference statements)
15
389
1
2
Order By: Relevance
“…Uninfected and infected hiPS-lt-NES cells were induced to differentiate by removal of growth factors and cultured in the presence of 1% FBS for 4 weeks. Both hiPS-lt-NES cell population differentiated into large and small numbers of Tuj1-positive neurons and GFAP-positive astrocytes, respectively, as observed in our previous study [11] (Fig. 1D).…”
Section: Characterization Of Hips-lt-nes Cells In Vitrosupporting
confidence: 85%
See 3 more Smart Citations
“…Uninfected and infected hiPS-lt-NES cells were induced to differentiate by removal of growth factors and cultured in the presence of 1% FBS for 4 weeks. Both hiPS-lt-NES cell population differentiated into large and small numbers of Tuj1-positive neurons and GFAP-positive astrocytes, respectively, as observed in our previous study [11] (Fig. 1D).…”
Section: Characterization Of Hips-lt-nes Cells In Vitrosupporting
confidence: 85%
“…We have previously shown that hiPS-NES cells, which are reliably derived from different hiPS cell lines, exhibit consistent characteristics such as continuous expandability, stable neuronal and glial differentiation, and the capacity to generate functional mature human neurons [11]. hiPS-lt-NES cells can be expanded in the presence of FGF2 and EGF in monolayer culture, and express the NSC markers Sox2 and Nestin (Fig.…”
Section: Characterization Of Hips-lt-nes Cells In Vitromentioning
confidence: 91%
See 2 more Smart Citations
“…In this context, we have recently described a population of hESC‐derived long‐term self‐renewing neuroepithelial stem cells (lt‐NES) 22, 23. Similar to pluripotent stem cells, this population exhibits strong self‐renewal capacity enabling genetic modification, subsequent clonal selection and expansion at a scale sufficient for potential therapy.…”
Section: Introductionmentioning
confidence: 99%